2016
DOI: 10.1016/j.rehab.2015.11.005
|View full text |Cite
|
Sign up to set email alerts
|

An alternative treatment for contractures of the elderly institutionalized persons: Microinvasive percutaneous needle tenotomy of the finger flexors

Abstract: Large-needle tenotomy seems safe and effective for treating claw hand in fragile older patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…The relevance of percutaneous needle tenotomy lies in the minimally invasive nature of the procedure underlined by several authors 18 : very short operating time (<10min per tendon), small cutaneous opening avoiding postoperative skin complications, possibilities to perform the gesture under local or locoregional anesthesia avoiding general anesthesia complications, and hospitalization (patients staying in the hospital for >1d) reduced to a strict minimum. Furthermore, this procedure does not impede the future possibility of performing open full tenotomy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The relevance of percutaneous needle tenotomy lies in the minimally invasive nature of the procedure underlined by several authors 18 : very short operating time (<10min per tendon), small cutaneous opening avoiding postoperative skin complications, possibilities to perform the gesture under local or locoregional anesthesia avoiding general anesthesia complications, and hospitalization (patients staying in the hospital for >1d) reduced to a strict minimum. Furthermore, this procedure does not impede the future possibility of performing open full tenotomy.…”
Section: Discussionmentioning
confidence: 99%
“…16 El Hage et al 17 reported a series of 27 children with severe brain damage operated with this technique for adductor longus contractures responsible for hip deformation. Schnitzler et al 18 published a report on 18 elderly patients with acquired deforming hypertonia treated with this technique for severe contracture of the finger flexors.…”
mentioning
confidence: 99%
“…In a prospective randomized trial of open versus US-guided percutaneous trigger finger release, the US-guided approach resulted in fewer days of work missed and better cosmetic results in comparison with the open surgery technique [56]. Percutaneous needle tenotomy has been used successfully to treat muscle and tendon contractures associated with neurological disorders as an alternative to surgical lengthening or release [59,60]. US guidance can be used to enhance needle guidance in these procedures.…”
Section: Us-guided Proceduresmentioning
confidence: 99%
“…However, several studies have been published on needle tenotomies performed on other indications e.g. talipes equino varus (clubfoot) in children, as a treatment of tendon contractures of patients with cerebral palsy and finger contractures of the institutionalized elderly patients [13], [14], [15].…”
Section: Introductionmentioning
confidence: 99%